Experimental analysis and pressureless sintering of powder processed functionally graded nickel alumina plates - Muhammad Ihsan, Abdul Latiff (2019)
Functionally graded material (FGM) is a class of advanced materials innovated particularly to address the issue of integrating different materials of dissimilar properties and resolve the inter-particle bonding problems by reducing the stress concentration between adjacent layers. Nickel-alumina (Ni/Al2O3) FGM system is famously recognized as heat resisting materials and stable at high temperature (above 1000ºC). In this research, multilayered Ni/Al2O3 FGM samples were designed and fabricated through powder metallurgy and pressureless sintering procedures and then were characterized in terms of their physical and microstructural properties. The research methodologies include preliminary numerical studies using finite element method (ANSYS) involving cylindrical plate of Ni/Al2O3 FGM. In the experimental procedures, cylindrical samples of 6 and 9 layered Ni/Al2O3 FGM samples were fabricated through powder metallurgy route, compacted at 414 MPa uniaxial pressure followed by pressureless sintering process at 1200ºC in argon atmosphere based on different processing parameters. The composition of each 4 and 7 graded interlayers, with respect to the Ni wt.% are 80, 60, 40 and 20 wt.% and 85, 70, 60, 50, 30, 20 and 10 wt.%, respectively. For each FGM sample, the sintering times were varied (3 hours and 4 hours) to compare the physical properties and microstructural evolution of the fabricated samples. Samples which were sintered for 4 hours showed better properties in terms of relative densities (57.64% and 62.06% respectively for 6 and 9 layered samples) and reduced porosities (42.36% for 6 layered samples and 37.94% for 9 layered samples). Shrinkage behavior in all samples increased as the composition of ceramic Al2O3 increase, while radial shrinkage of 6 layered samples showed more changes compared to 9 layered samples due to larger differences in resultant thermal expansion between layers. Nevertheless, the microhardness results were not in satisfactory level as expected and the hardness values were declining although the ceramic composition was increased in each layer. This is due to the incomplete transformation of alumina into hard ceramic and increasing of porosities in the graded structure as the ceramic content rises. Optical micrographs revealed uniform distribution of nickel and alumina particles in each layer as well as parallel interface which confirmed proper blending and pressing processes. The uniformities were supported by the Energy Dispersive X-Ray Spectroscopy (EDS) analyses. The optical micrographs also exhibited gradual microstructural transition characteristics from pure metal to pure ceramic with the addition in the ceramic fraction from a ceramic-dispersed type structure, followed by a network type and subsequently alternate dispersive structure of metallic phase in the ceramic matrix. Micrographs of Scanning Electron Microscopy (SEM) analyses further revealed the presences of micro pores and micro cracks especially in the alumina-rich structures. However, in some samples it was evident that there were fewer pores observed in the structure of samples sintered for 4 hours sintering time compared to those of 3 hours. Therefore it is suggested that 4 hours sintering time will allow more inter-particle connectivity and bonding to take place.